Assessing multidimensional complexity in home care: congruencies and discrepancies between patients and nurses - Catherine Busnel; Fanny Vallet; Eleni-Marina Ashikali; Catherine Ludwig (BMC, 2022)
Abstract Background Person-centered care allows for the inclusion of the totality of a person's needs and preferences, beyond just the clinical or medical aspect. This approach requires the development of tools to allow for the integration of the patient in his/her healthcare. Based on a 30-item tool developed for nurses to evaluate the complexity of home care situations (COMID), this study proposed a version for the patients (i.e. COMID-P). Both instruments were used, independently by nurses and patients, to rate the complexity of individual situations, in order to compare ratings. Methods The COMID-P and the COMID were completed during the fraXity study at the patients' homes, independently by patients (aged 65 and over) and nurses. Item-level and scale-level analyses were performed using, Kappa and McNemar tests, and intra-class correlation (ICC). Results A total of 159 pairs of COMID and COMID-P ratings were retained for analyses. Results demonstrated a high degree of patient/nurse agreement for 12/30 items, a moderate agreement for 10/30 items, and a low degree of agreement for 7/30 items. The intra-class correlation between the COMID-P and the COMID was high (ICC= .826, 95%CI [.761-.873]). Conclusions The results demonstrate that patients and nurses can assess complexity using tools that have comparable structural properties. They also reveal congruencies and discrepancies in scoring the components of complexity, highlighting the need of reaching consensus in designing care plans. Further work is needed to demonstrate the benefits of joint assessment in developing care plans that truly meet patients' needs. Trial registration The fraXity study was registered in ClinicalTrials.gov, NCT03883425 , on March 20, 2019.